Identification of Economic and Social Measures on Reformation of Urban Eroded Context (Case Study: Shahr-E-Kord City Eroded Context) - Ghaed Amini, Morteza; Vadayeh Kheyri, Roghayeh (International Journal of Engineering and Technology, 2018)
Cities are alike living beings that are consistently in need of instauration and require restoration and reconstruction of withered tissues and replacement of new cells with the old ones. The eroded context of Shahr-e-kord city is one of the eroded and valuable fabric samples which is facing social, economic, and skeletal evolutions due to problems such as social and economic degradation, skeletal erosion, etc. Given that, the subject of this research that is the reformation of Shahr-e-kord eroded context was chosen and reviewed due to the significance of social and economic studies.Achieved findings from final evaluation through SWOT factors in of AHP model depicts that in strength points, long settlement of peopleâ€™s in context and integration of available potentials in context for reformation are the most important strengths, and the population mitigation in area and descending value of its functions are the most important threats.Today, the main problem of under study context is the low affordability and disproportion of expenses and incomes of families in eroded context. Based on final analyses in this research, substantial propositions to benefit from the strengths, opportunities, declination of weaknesses and threats in form of SWOT model strategies are suggested for reformation of Shahr-e-kord eroded context.Â Â